Actin cytoskeleton differently regulates cell surface organization of GPI-anchored proteins in polarized epithelial cells and fibroblasts - Lebreton, Stéphanie; Paladino, Simona; Lelek, Mickaël; Tramier, Marc; Zimmer, Christophe; Zurzolo, Chiara (Frontiers in Molecular Biosciences, 2024)
The spatiotemporal compartmentalization of membrane-associated glycosylphosphatidylinositol-anchored proteins (GPI-APs) on the cell surface regulates their biological activities. These GPI-APs occupy distinct cellular functions such as enzymes, receptors, adhesion molecules and they are implicated in several vital cellular processes. Thus, unravelling the mechanisms and regulators of their membrane organization is essential.In polarized epithelial cells, GPI-APs are enriched at the apical surface, where they form small cholesterol-independent homoclusters and larger heteroclusters accommodating multiple GPI-AP species, all confined within areas of approximately 65-70 nm in diameter. Notably, GPI-AP homoclustering occurs in the Golgi apparatus through a cholesterol-and calcium-dependent mechanism that drives their apical sorting. Despite the critical role of Golgi GPI-AP clustering in their cell surface organization and the importance of cholesterol in heterocluster formation, the regulatory mechanisms governing GPI-AP surface organization, particularly in the context of epithelial polarity, remain elusive. Given that the actin cytoskeleton undergoes substantial remodeling during polarity establishment, this study explores whether the actin cytoskeleton regulates the spatiotemporal apical organization of GPI-APs in MDCK cells. Utilizing various imaging techniques (Number&Brightness, FRET/FLIM, dSTORM), we demonstrate that the apical organization of GPI-APs, at different scales, do not rely on the actin cytoskeleton, unlike in fibroblastic cells. Interestingly, calcium chelation disrupts the organization of GPI-APs at the apical surface by impairing Golgi GPI-AP clustering. In summary, our findings unveil distinct mechanisms regulating the organization of GPI-APs in cell types of different origins, plausibly allowing them to adapt to different external signals and different cellular environment in order to achieve specialized functions.